Associations between nephrolithiasis and diabetes mellitus, hypertension and gallstones: A meta‐analysis of cohort studies - Lin, Bing‐Biao; Huang, Rong‐Hua; Lin, Bing‐Liang; Hong, Ying‐Kai; Lin, Ming‐En; He, Xue‐Jun (Nephrology (Carlton, Vic.), 2020)
Aim To review and clarify the strengths and directions of associations between nephrolithiasis and hypertension (HTN), diabetes mellitus (DM) and gallstones (GS) given the inconsistent results reported in cohort studies. Methods Relevant literature was searched in PubMed and EMBASE from inception to July 2019, for cohort studies that examined the relationships between kidney stones and these three diseases among adults. Pooled relative risks (RRs) were calculated by maximally adjusted risk estimates using a random effect model. Subgroup analysis, meta‐regression and sensitivity analysis were conducted whenever appropriate. Results Of 3537 papers, 21 articles with each including 1 to 3 cohorts were identified. In this meta‐analysis, nephrolithiasis was reciprocally linked to HTN, DM and GS. Kidney stones were significantly associated with 31%, 33% and 46% higher risks of incident HTN, DM and GS whereas GS was associated with a significantly higher risk of nephrolithiasis (RR: 1.49; 95% CI, 1.28‐1.73), followed by HTN (RR: 1.30; 95% CI, 1.11‐1.52) and DM (RR: 1.18; 95% CI, 1.07‐1.29). Also, females with DM (RR: 1.29; 95% CI, 1.08‐1.55) were more likely to develop kidney stones than diabetic male patients (RR: 0.91; 95% CI, 0.75‐1.10). Conclusion Although additional studies are needed to confirm these findings and elucidate the mechanisms, this study revealed possible bidirectional associations between nephrolithiasis and HTN, diabetes and GS, which reinforced the notion of nephrolithiasis as a systemic disease that requires comprehensive investigations. SUMMARY AT A GLANCE This systematic review and meta‐analysis demonstrates a bidirectional association between nephrolithiasis with hypertension, diabetes mellitus and gallstones. Due to a substantial between‐study heterogeneity and possible publication bias, further studies are needed to confirm the mechanistic links between kidney stones and other metabolic disorders.